Characterisation of weathered hydrocarbon wastes at contaminated sites by GC- simulated distillation and nitrous oxide chemical ionisation GC/MS, with implications for bioremediation - Pollard, Simon J. T.; Hrudey, Steve E.; Rawluk, Marv; Fuhr, Bryan J. (Royal Society of Chemistry, 2004)
An extended analytical characterisation of weathered hydrocarbons isolated from historically contaminated sites in Alberta is presented. The characterisation of soil extracts, chromatographically separated into component classes, by GC- simulated distillation and nitrous oxide (N2O) chemical ionisation (CI) GC-MS provides new insights into the composition of the residual oil at these sites, the principal partition medium for risk critical components. The combined polar and asphaltene content of representative soil extracts ranged from 40% w/w to 70% w/w of the oils encountered. An abundance of C14–C22 2–4 ring alicyclics, alkylbenzenes and benzocycloparaffins is prevalent within the saturate fractions of site soils. Implications for the partitioning of risk critical compounds at sites with weathered hydrocarbons and the practical application of bioremediation technologies are discus